Development of ClassPoint Based Interactive Learning Media for Improving Students Cognitive Abilities - Masruroh, Dewi; Ihsani, Ade Novi Nurul; Suryatna, Bambang Sugeng; Sutopo , Yeri (Universitas Negeri Semarang, 2025)
Vocational High Schools, particularly Beauty and Spa programs, play a crucial role in preparing students for the workforce. However, preliminary observations indicate that learning in the Spa and Beauty Industry Profile element still utilizes conventional media (lectures, static PowerPoint presentations), resulting in minimal interactivity, student passivity, low motivation, and low cognitive achievement. This study aims to develop interactive learning media based on ClassPoint to improve students' cognitive abilities in the Spa and Beauty Industry Profile element. The method used is the ADDIE Research and Development (R&D) model through the stages of analysis, design, development, implementation, and evaluation. The product was validated by three media experts and three material experts, and its effectiveness was tested through pre- and post-tests on 60 students in the control and experimental classes. The results showed that the media was declared very feasible by the media experts with an average score of 4.27 and very appropriate by material experts with a score of 4.46. The independent t-test showed a significant difference in learning outcomes after treatment, and the effectiveness test showed an N Gain score of 83% in the experimental class, higher than the control class. It can be concluded that interactive learning media based on ClassPoint valid, appropriate, and effective for improving students' cognitive abilities in learning.